2009
DOI: 10.5539/ijef.v1n2p45
|View full text |Cite
|
Sign up to set email alerts
|

ASEAN-5 + 3 and US Stock Markets Interdependence Before, During and After Asian Financial Crisis

Abstract: The issues of international stock markets linkages had been investigated over the time. Since the Asian financial crisis in 1997, many economists are concerned about the relationship between Asian stock markets and others in the world. This paper is conducted to examine the linkages between ASEAN-5+3 namely Malaysia, Singapore, the Philippines, Thailand, Indonesia, China, Japan and Korea and US stock markets. The data consists of weekly stock indices data. The total samples are separated into three subperiods.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 17 publications
1
7
0
1
Order By: Relevance
“…Meanwhile, Qatar, Saudi Arabia, UAE and Bangladesh sharia stock market models have an F-statistic value below the lowest critical value (lower bound), so it can be concluded that there is no co-integration on all models. These findings are consistent with research by Royfaizal et al (2009), Kassim (2013), Nurrachmi (2019), Majid et al (2008) and Jiang et al 2017 which proves that the stock price index is co-integrated in the crisis period.…”
Section: China Stock Market Crisis Periodsupporting
confidence: 92%
“…Meanwhile, Qatar, Saudi Arabia, UAE and Bangladesh sharia stock market models have an F-statistic value below the lowest critical value (lower bound), so it can be concluded that there is no co-integration on all models. These findings are consistent with research by Royfaizal et al (2009), Kassim (2013), Nurrachmi (2019), Majid et al (2008) and Jiang et al 2017 which proves that the stock price index is co-integrated in the crisis period.…”
Section: China Stock Market Crisis Periodsupporting
confidence: 92%
“…The connections among the ASEAN-3+5 countries (China, Japan, Korea, Malaysia, Singapore, the Philippines, Thailand, Indonesia) and US stock exchanges for the time period of 1997 Asian financial crisis analysed by Royfaizal, Lee, Azali, (2009) using Granger Causality test. It was found that ASEAN-3+5 and US stock markets are related each other for the global financial crisis and post-crisis periods.…”
Section: Brief Literature Reviewmentioning
confidence: 99%
“…Local financial institutions witnessed lack of liquidity and deterioration in the local currency exchange, and most of the stock markets collapsed, causing market values to sharply drop among others . These negative effects were due to the weak domestic financial system, the contagion effects of changing market sentiment, free international capital flows, and inconsistent economic policies (Royfaizal et al, 2009). All these factors offer substantial opportunities for speculators to make profit in the short term by speculating the financial markets of Asian region causing the 1997/1998 financial crisis.…”
Section: Introductionmentioning
confidence: 99%